2004
DOI: 10.1074/jbc.m313575200
|View full text |Cite
|
Sign up to set email alerts
|

Purinergic Receptors Coupled to Intracellular Ca2+ Signals and Exocytosis in Rat Prostate Neuroendocrine Cells

Abstract: Rat prostate neuroendocrine cells (RPNECs) display a variety of ion channels and exhibit

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
14
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 34 publications
(44 reference statements)
2
14
0
Order By: Relevance
“…This is consistent with findings of recent studies in which ATP agonists resulted in the internalization of biotinylated P2X 1 receptors (59) and activation of a P2X 7 -like receptor in thymocytes stimulated exocytosis and endocytosis (60). Similarly, endocytosis of P2Y receptors is stimulated by addition of uridine (61), and activation of P2Y receptors may lead to endocytosis in prostate neuroendocrine cells (43). Although it is preliminary, we believe this to be the first evidence demonstrating that ATP signaling may be involved in regulation of pressure-induced endocytosis in bladder umbrella cells.…”
Section: Figuresupporting
confidence: 80%
See 1 more Smart Citation
“…This is consistent with findings of recent studies in which ATP agonists resulted in the internalization of biotinylated P2X 1 receptors (59) and activation of a P2X 7 -like receptor in thymocytes stimulated exocytosis and endocytosis (60). Similarly, endocytosis of P2Y receptors is stimulated by addition of uridine (61), and activation of P2Y receptors may lead to endocytosis in prostate neuroendocrine cells (43). Although it is preliminary, we believe this to be the first evidence demonstrating that ATP signaling may be involved in regulation of pressure-induced endocytosis in bladder umbrella cells.…”
Section: Figuresupporting
confidence: 80%
“…We previously demonstrated that exocytosis in umbrella cells is stimulated by agents that increase intracellular Ca 2+ or cAMP production (26,28). Upon ATP binding, P2X receptor activation can result in increased levels of intracellular Ca 2+ , a result of Ca 2+ influx from outside the cell and release of Ca 2+ from intracellular stores (14,(42)(43)(44). Increased levels of intracellular Ca 2+ can also activate some isoforms of adenylyl cyclase (45), resulting in increased cAMP production and activation of the cAMP effector PKA.…”
Section: Figurementioning
confidence: 99%
“…The P2 receptor antagonist, suramin, attenuates nerve-mediated contractions of the guinea-pig prostate [225]. P2 receptors have been shown to be present in the human prostate, including P2Y 1 receptors [181] and P2X1 receptors [205,244]. P2X1 receptors were also expressed in the rat prostate [227].…”
Section: Prostatementioning
confidence: 99%
“…The P2 receptor antagonist suramin attenuated nerve-mediated contractions of the guinea-pig prostate (Lau et al, 1998) suggesting involvement of P2 receptors, which have been shown to be present in the prostate (Janssens et al, 1996;Morikawa et al, 2007). Additional candidates are P2X receptors; in mature rats the P2X 1 receptor is found in smooth muscle cell membranes of the prostate (Kim et al, 2004;Lee et al, 2000;Longhurst et al, 1996), and the P2X 3 receptor is found in nerve fibers of the prostate interstitial connective tissue . Either or both could be involved in the regulation of contractions of the prostate during ejaculation.…”
Section: Prostatementioning
confidence: 93%